Mao. 15 - Takahashi, Rumiko, 1957-; Garrity, Shaenon K. (Shōnen Sandē komikkusu., 2024)
"When Nanoka is transported back in time to a supernatural early 20th century, she gets recruited by aloof exorcist Mao. What thread of fate connects them? Together, they seek answers...and kick some demon butt along the way! Just when it seems that the mystery of Sana's death has been solved, surprising details come to light that change everything. The identity of the zombie body that Byoki revived is finally revealed. Then, the gang helps Kamon investigate the peril that befalls his fiancée and tracks the dissemination of his creation, the Seed of Haku"--Back cover.